Acute toxicity of lead to Penaeus monodon postlarvae. - Serra, Sheila Jamelo
Acute toxicity test of Lead (Pb) to 22-day old Panaeus monodon postlarvae was conducted using static bioassay method. The median lethal concentration or LC50 were 3.26ppm, 2.72ppm, 2.41ppm and 1.96ppm for 24-h, 48-h, 72-h and 96-h respectively. LC50 decreases with time of exposure. Mortality was found to be highest during the first 4 hours of exposure and fluctuates within the succeding hours.